Building student’s political behaviour in the context of election in Indonesia - Abdullah, M; Hakam, K A; Wilodati; Ratnafitria (IOP conference series. Earth and environmental science, 2021)
The electoral process in Indonesia is a system that be built in democracy of typical politics of Indonesia and it cannot be separated from decision-making due to the voters. This decision-making in determining the choice on any individual voters cannot be separated from their social characteristics, so did the same with the students. Problems that appear then is the social characteristic of the students impact on terms of their political attitudes in elections? How to build the student’s political behavior in election? Through the application of descriptive study design with a quantitative approach and take the subject of research on students of UPI, this study tries to assess the contribution social characteristics of the students to their political behavior in election that be reviewed from the perspective of political geography. In general, the results indicate that the student’s political behavior tended to be rational. Meanwhile, the loyalty and/or fanatic attitude to the one is not to be seen. Here it can be seen that the social environment and education as the social characteristic of the society, especially on the students, contribute in forming their political behavior quite enough. Thus, it is time for the public awareness and political behavior be constructed and trained for always in line with the interests of the nation political advance.